Ecoturismo en Pradera Valle del Cauca como elemento articulador de municipios con déficit de infraestructura para el turismo. (2022)
The following project addresses ecotourism as the main topic, defining it as a tourist recreation activity in natural ecological zones with a high degree of incidence of the ecosystem in its natural state, potential for this activity.